Investigating the critical success factors of lean implementation in UUM Library - Wong, Li Sheng (Universiti Utara Malaysia, 2020)
Today, many organizations in the manufacturing sector has used the Lean approach to reduce their cost and increase productivity. However, only a few service sectors implement the Lean approach including the academic library. Since some of the service sectors have implemented lean, there would be critical success factors to lean implementation. This study aims to identify the Critical Success Factors (CSFs) of Lean implementation in the UUM library. Besides that, this study tends to investigate the benefits and the effects of the Lean management implementation on the operation of the library. The data were collected via interview, and literature review. The interview targeting quality system management staff of the UUM library and have been analyzed with qualitative technique. This study has indicated that the leadership, financial capability, organization culture, and expert skill are the CSFs of Lean implementation in the UUM library. It is concluded that these factors are need in Lean implementation in the academic library. Since this is a preliminary study, more empirical works need to be done for future study.